Maxwell's handbook for RDA : explaining and illustrating RDA, Resource description and access, using MARC21 - Maxwell, Robert L., 1957- (Chicago, Illinois : American Library Association, 2013)
In this clear and comprehensive resource, cataloging expert Robert Maxwell brings his trademark practical commentary to bear on the new, unified cataloging standard. Designed to interpret and explain RDA: Resource Description and Access, this handbook illustrates and applies the new cataloging rules in the MARC21 environment for every type of information format. From books to electronic materials to music and beyond, Maxwell Explains the conceptual grounding of RDA, including FRBR and FRAD Addresses the nuances of how cataloging will, and won't, change in the MARC21 environment Shows catalogers how to create and work with authority records of persons, families, corporate bodies, geographic entities, works, and expressions Explores recording relationships, working with records of manifestations and items, and more Provides numerous sample records to illustrate RDA principles A guided tour of the new standard from a respected authority, this essential handbook will help catalogers, LIS students, and cataloging instructors navigate RDA smoothly and find the information they need efficiently.
Includes bibliographical references and index.
Keywords: Resource description & access -- Handbooks, manuals, etc; Descriptive cataloging -- Rules -- Handbooks, manuals, etc; MARC formats -- Handbooks, manuals, etc